تحديد مصطلح النحو ودور تاريخه في تدوير اللغة العربية - Sulaikho, Siti; Setyawan, Cahya Edi (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2024)
The objective of this research was to reveal seven sections, namely the definition of nahwu, the identification of the term nahwu, its implications and section, the time of the development of the science of nahwu, and its status was purely Arab or influenced by other cultures of nations other than the Arabs, and the author of the first nahwu, and the reason for the emergence of nahwu, and the role of nahwu and its history in the development of Arabic language education. The model in this paper is explanatory. Its approach is qualitative. Data collection techniques are documents. The data analysis in this research followed four steps from Miles and Huberman. This research concludes that the definition of nahwu is the intention. It has nine other meanings. Defining the term nahwu is the change that follows the end of the word. As for the status of nahwu, there are two different opinions, and they are in the first version of Islam and nahwu is in the Arabs older than the first version of Islam. Scientists went on to develop the science of nahwu. First, they agree that the status of nahwu is purely Arabic. Second, they see nahwu as a transfer from the Greek language. Third, they believe nahwu was initially purely Arabic and later influenced by Greek philosophy. As for the first author of the science of nahwu, most scholars agree that the first author of the science of nahwu is Abu Al-Aswad Al-Du'ali by order of Ali bin Abi Talib. The reason for the emergence of nahwu is the distortion of the melody and the corruption of tongues after the spread of Islam and the mixing of Arabs with other nations that embraced Islam. As for the role of nahwu and its history in the development of Arabic language teaching, there are two opinions. The first mixed in the research of nahwu, derivation and morphology, or derivation and morphology. The second was in Arabic sciences three sciences. They are nahwu or grammar, derivation, and morphology. These three sciences are still taught and taught under one name, nahwu.